Supressão de Meloidogyne sp. por isolados de Trichoderma, na soja - Wohlenberg, Maísa Didoné (2018)
Plant-parasitic nematodes are worms that parasitize plants. The genus Meloidogyne sp. is considered the most cosmopolitan and polyphagous among plant-parasitic nematodes, causing great damage in crops of agricultural importance, such as soybeans. Several control methods are used to contain the damage of this pathogen, among them the biological control with nematophagous fungi. The objective of this study was to evaluate the effect of the fungus Trichoderma spp. in the suppression of Meloidogyne sp., in the establishment of the crop, production of fresh / dry matter and attributes of chlorophyll a, through the microbiolization of soybean seeds. Laboratory tests were carried out to isolate fungus of the genus Trichoderma spp. of soils infested with Meloidogyne sp. In vitro tests were execute out to measure juvenile mortality and egg hatching of Meloidogyne javanica under the action of Trichoderma spp. Two experiments were execute out under greenhouse conditions. In the first experiment, two isolates of Trichoderma spp. with three doses, 0.25x108, 1.25x108 and 2.50x108 conidia per 50 g-1 of seed for suppression of M. incognita. In the second experiment three Trichoderma spp. with three doses, 0.25x108, 1.25x108 and 2.50x108 conidia per 50 g-1 of seed for the suppression of M. javanica. The rate of germination and germination, root dry matter and penetration of second stage juveniles of M. javanica were measured. In the period of soybean flowering, chlorophyll a fluorescence, fresh/dry matter of shoot and root, number of galls, egg mass number and reproduction factor of M. incognita and M. javanica were measured. The Trichoderma’s isolate UFSMQ36 2.50x108 conidia was effective in the suppression of M. incognita. The same isolate Trichoderma 1.25x108 conidia, showed positive results for the dry matter of shoots and attributes chlorophyll a fluorescence. The Trichoderma’s isolates UFSMQ1 and UFSMQ40 promoted the mortality of juveniles of second stage of Meloidogyne javanica in vitro. The Trichoderma UFSMQ1 and UFSMQ40 suppressed the activity of M. javanica. The highest possible amount evaluated in this Trichoderma UFSMQ40 inoculum study favored the suppression of M. javanica. The UFSMQ36 isolate provided higher germination, germination velocity index and electron transport rate.